Two Shades of Cringe: Problems in Attributing Painful Laughter - Patrick Wöhrle (Humanities, 2021)
This article aims to approach the phenomenon of cringe in four steps: First, from a sociological perspective, the distinction between shame and embarrassment is discussed and a working definition is developed that conceives of this difference as situational rather than essential. In a second step, this distinction will be used to examine more closely how the actors’ self-representation is decomposed in the reality format Wife Swap and what role cringe—understood as “Fremdscham” or “vicarious embarrassment”—plays in this. Third, an explanation for the attractiveness of these formats is offered that draws on the concept of “flexible normalism” and further specifies the latent functions of these formats sociologically. Finally, with a look at current cringe comedy, it is elaborated that the use of cringe as made in Wife Swap is a very restricted and truncated variety of this phenomenon. Cringe in a comprehensive sense, meanwhile, turns out to be a reflexive resource based on an unresolved ambiguity of multiple and often intersecting attributions.